Does surface coating of metallic nanoparticles modulate their interference with in vitro assays?1. Issue 87 (20th September 2015) - Vinković Vrček, Ivana; Pavičić, Ivan; Crnković, Tea; Jurašin, Darija; Babič, Michal; Horák, Daniel; Lovrić, Marija; Ferhatović, Lejla; Ćurlin, Marija; Gajović, Srećko
<x xml:space="preserve">Abstract</x> Experimental setup for in vitro evaluation of metallic nanoparticles where interferences depend on metal core, surface coating, and the test system.